Design of Robust Power System Stabilizer Considering Less Control Energy - Cuk Supriyadi Ali Nandar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper proposes design a robust power system stabilizer (PSS) considering less control energy using a genetic algorithm (GA). The structure of proposed PSS is a 1st-order lead-lag compensator, it is easy to implement in power system utility. In the design, system uncertainties are modeled by an inverse additive uncertainty. The performance, robust stability condition, and less control energy of the designed system are formulated as the objective function in the optimization problem. The GA is applied to solve an optimization problem and to achieve control parameters of proposed PSS. The performance and robustness against system uncertainties of the proposed PSS are investigated in the single-machine infinite bus system in comparison with a conventional PSS and a PSS designed by fixed-structure H∞ loop shaping. Simulation results show that with less control energy, the robustness and damping effect of the proposed PSS can be guaranteed against various operating conditions.Keywords: Control system design, operation and control of power systems, robust control application, less control energyDOI: http://dx.doi.org/10.11591/ijpeds.v2i1.143